Supplementary material 2 from: Put JE, Put L, St. Clair CC (2017) Caching behaviour by red squirrels may contribute to food conditioning of grizzly bears. Nature Conservation 21: 1-14. https://doi.org/10.3897/natureconservation.21.12429 - Put, Julia Elizabeth; Put, Laurens; St. Clair, Colleen Cassady (Zenodo, 2017)
Data collected along transects : Data type: specimens data